2012
DOI: 10.1016/j.devcel.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule-Associated Rho Activating Factor GEF-H1 Interacts with Exocyst Complex to Regulate Vesicle Traffic

Abstract: SUMMARY The exocyst complex plays a critical role in targeting and tethering vesicles to specific sites of the plasma membrane. These events are crucial for polarized delivery of membrane components to the cell surface, which is critical for cell motility and division. Though Rho GTPases are involved in regulating actin dynamics and membrane trafficking, their role in exocyst-mediated vesicle targeting is not very clear. Herein, we present evidence that depletion of GEF-H1, a guanine nucleotide exchange factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 41 publications
(53 reference statements)
3
70
0
1
Order By: Relevance
“…Although our data indicate that Cdc42 is downregulated by the exocyst-mediated delivery of Cdc42GAP, previous data has shown that Cdc42 reciprocally regulates the exocyst complex during bacterial invasion (Mohammadi and Isberg, 2013;Wu et al, 2008). Other work has shown that the exocyst complex controls the activity of the Rho GTP-binding proteins Rac and Rho through a presumed direct interaction with the Rac GAP SH3BP1 or the Rho GEF H1 (also known as ARHGEF2) with consequences for cell migration (Parrini et al, 2011) or vesicle trafficking (Pathak et al, 2012), respectively. Although we demonstrate here that the functional interaction of Cdc42GAP with Cdc42 requires the exocyst complex, we could not coimmunoprecipitate Cdc42GAP with any exocyst complex protein, nor could we detect a direct interaction of purified Cdc42GAP with any exocyst complex protein, despite intensive efforts.…”
Section: Discussionmentioning
confidence: 46%
“…Although our data indicate that Cdc42 is downregulated by the exocyst-mediated delivery of Cdc42GAP, previous data has shown that Cdc42 reciprocally regulates the exocyst complex during bacterial invasion (Mohammadi and Isberg, 2013;Wu et al, 2008). Other work has shown that the exocyst complex controls the activity of the Rho GTP-binding proteins Rac and Rho through a presumed direct interaction with the Rac GAP SH3BP1 or the Rho GEF H1 (also known as ARHGEF2) with consequences for cell migration (Parrini et al, 2011) or vesicle trafficking (Pathak et al, 2012), respectively. Although we demonstrate here that the functional interaction of Cdc42GAP with Cdc42 requires the exocyst complex, we could not coimmunoprecipitate Cdc42GAP with any exocyst complex protein, nor could we detect a direct interaction of purified Cdc42GAP with any exocyst complex protein, despite intensive efforts.…”
Section: Discussionmentioning
confidence: 46%
“…GEF-H1 was also proposed to promote Rho activation at the leading edge and locally favor actin polymerization and lamellipodium protrusion in 2D (Nalbant et al, 2009). However, GEF-H1 action might be more complicated because it is possibly also a Rac1 GEF (Callow et al, 2005;Ren et al, 1998) and involved in exocytosis -a process that was mentioned above as a putative cell motility regulator (Pathak et al, 2012). Moreover, feedback mechanisms have been described whereby Rac1 stabilizes microtubules by inhibiting the microtubule-destabilizing protein stathmin (STMN1) (Steinmetz, 2007) through p21-activated kinase 1 (PAK1) (Wittmann et al, 2003(Wittmann et al, , 2004.…”
Section: Microtubule-related Signaling In 3d Environmentsmentioning
confidence: 99%
“…Mycoplasma tests were performed every two months. The Rab8Q67L-GFP, Rab8WT-GFP, Rab8 mut -mRFP and constitutively active GEF-H1 c53r constructs were as described previously (Bravo-cordero et al, 2007;Pathak et al, 2013). The Rab8 rescue construct (Rab8 mut ) carries four silent mutations in the Rab8 shRNA target sequence.…”
Section: Cell Culture Transfection and Stable Cell Line Generationmentioning
confidence: 99%